2016
DOI: 10.1002/adfm.201504051
|View full text |Cite
|
Sign up to set email alerts
|

Light and Strong SiC Networks

Abstract: The directional freezing of micro-fiber suspensions is used to assemble highly porous (porosities ranging between 92 to 98%) SiC networks. These networks exhibit a unique hierarchical architecture in which thin layers with honeycomb-like structure and internal strut length in the order of 1 to 10 µm in size are aligned with an interlayer spacing ranging between 15 to 50 microns. The resulting structures exhibit strengths (up to 3 MPa) and stiffness (up to 0.3 GPa) that are higher than aerogels of similar densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 51 publications
1
99
0
2
Order By: Relevance
“…Ferraro et al [55] reported that SiC fibers can be assembled into highly porous networks by the freeze-casting technique, as shown in Figure 4A. After sintering at 1800 °C under an argon atmosphere, the resultant scaffold showed a structure with a highly interconnected porosity and a hierarchical architecture with aligned thin and porous ceramic layers.…”
Section: Nanofibers For Assembling Bioinspired Materials By Freeze Camentioning
confidence: 98%
“…Ferraro et al [55] reported that SiC fibers can be assembled into highly porous networks by the freeze-casting technique, as shown in Figure 4A. After sintering at 1800 °C under an argon atmosphere, the resultant scaffold showed a structure with a highly interconnected porosity and a hierarchical architecture with aligned thin and porous ceramic layers.…”
Section: Nanofibers For Assembling Bioinspired Materials By Freeze Camentioning
confidence: 98%
“…The first idea is to use anisotropic objects such as platelets or fibers. If properly controlled, the freeze front can align and orient the anisotropic objects, and thus induce preferential orientations in the structure [28,29], but also create lightweight, percolating fiber scaffolds (SiC, cellulose) [30,31]. The alignment of objects can be used later to obtain specific morphologies and thus microstructures [32] and improves structural or functional properties.…”
Section: Self-organisation Self-assemblymentioning
confidence: 99%
“…can we sinter these materials properly?) but can also be used to develop particular textures [32] or architectures [30]. We badly need experimental observation of crystal growth and particle redistribution at particle scale.…”
Section: Fundamental Understanding Of the Processmentioning
confidence: 99%
“…Moreover, it demonstrates that the NC-RUS technique and procedures developed in this thesis work, adds a significant value to materials characterization not only in synthetic materials but also in biological tissues such plant leaves, where it is possible to infer the microstructure in a non-destructive and non-invasive way. Ferraro et al 2016; 2, Sekisui Alveo. Alveolit®; 3, Álvarez-Arenas 2003; 4, Álvarez-Arenas et al 2002; 5, Sancho-Knapik, Peguero-Pina, Medrano, et al 2013;Farinãs et al 2013; 6, Necumer, Necuron®; 7, IEEE International Ultrasonic Symposium 2016 La Espectroscopía Ultrasónica Resonante Sin Contacto (NC-RUS, por sus siglas en inglés) ha demostrado ser una técnica muy efectiva para la caracterización de materiales que, en el caso particular del estudio de hojas de plantas, nos da información relevante acerca de los tejidos que las constituyen y que, en algunos casos, puede relacionarse con medidas obtenidas mediante métodos alternativos.…”
Section: Guillermo Fésserunclassified
“…dando lugar, en consecuencia, a un amplio rango de propiedades mecánicas como conocemos que en realidad existen en los materiales vegetales (ver Figura 3). Ferraro et al 2016; 2, Sekisui Alveo. Alveolit®; 3, Álvarez-Arenas 2003; 4, Álvarez-Arenas et al 2002; 5, Sancho-Knapik, Peguero-Pina, Medrano, et al 2013;Farinãs et al 2013; 6, Necumer, Necuron®; 7, IEEE International Ultrasonic Symposium 2016.…”
unclassified